Portuguese wine sme competitiveness- entry strategy for Germany and South Korea - Silva, Maria Beatriz De Jesus (2021)
Abstract: The present paper intends to develop an internalization proposal at Pimentel, a Portuguese SME operating in the wine industry. After a considerable analysis of possible market prospects to expand, Germany and South Korea ascended as countries chosen to design a business model. The analysis is conducted by choosing the most suitable entry mode for each market having in consideration cultural and contractual considerations inherent to each country, and marketing recommendations that fulfil the business plan and roadmap. Following this breakdown, Direct Exporting, realizes Pimentel current needs in both internalization strategies, notwithstanding an eventual method upscale.